Método de medición no lineal para medir deformaciones mecánicas de materiales y estructuras - Benítez, Julio César; Fernández, Germán Roberto; Grosz, Diego Fernando; Linale, Nicolás Martín; Sparapani, Alexis Cristian (2023)
Benítez, Julio César